Anonymity and Self-Expression in Online Rating Systems - An Experimental Analysis - Hoyer, Britta; van Straaten, Dirk (Journal of Behavioral and Experimental Economics)
Keywords: General Social Sciences; Economics and Econometrics; Applied Psychology

Network Disruption and the Common-Enemy Effect - Hoyer, Britta; De Jaegher, Kris (International Journal of Game Theory)

Gender, competitiveness, and task difficulty: Evidence from the field - Hoyer, Britta; van Huizen, Thomas; Keijzer, Linda; Rezaei, Sarah; Rosenkranz, Stephanie; Westbrock, Bastian (Labour Economics)
This study examines the gender gap in competitiveness in an educational setting and tests whether this gap depends on the difficulty of the task at hand. For this purpose, we administered a series of experiments during the final exam of a university course. We confronted three cohorts of undergraduate students with a set of bonus questions and the choice between an absolute and a tournament grading scheme for these questions. To test the moderating impact of task difficulty, we (randomly) varied the difficulty of the questions between treatment groups. We find that, on average, women are significantly less likely to select the tournament scheme. However, the results show that the gender gap in tournament entry is sizable when the questions are relative easy, but much smaller and statistical insignificant when the questions are difficult.

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja (Games and Economic Behavior)
We analyze the actual behavior of agents in a matching mechanism, using data from a clearinghouse at the Faculty of Business Administration and Economics at a German university, where a variant of the Boston mechanism is used. We supplement this data with data generated in a survey among the students who participated in the clearinghouse. We find that under the current mechanism over 74% of students act strategically by misrepresenting at least one of their preferences. Nevertheless, not all students are able to improve their outcome by doing so. We show that this is mainly due to the incomplete information of students and naiveté. Sophisticated students actually reach significantly better outcomes than naive students. Thus, we find evidence that naive students are exploited by sophisticated students in an incomplete information setting.

Price competition and the Bertrand model: The paradox of the German mobile discount market - Kaimann, Daniel; Hoyer, Britta (Applied Economics Letters)
We investigate the degree of price competition among telecommunication firms. Underlying a Bertrand model of price competition, we empirically model pricing behaviour in an oligopoly. We analyse panel data of individual pricing information of mobile phone contracts offered between 2011 and 2017. We provide empirical evidence that price differences as well as reputational effects serve as a signal to buyers and significantly affect market demand. Additionally, we find that brands lead to an increase in demand and thus are able to generate spillover effects even after price increase.

The Common Enemy Effect under Strategic Network Formation and Disruption - Hoyer, Britta; Haller, Hans (Journal of Economic Behavior & Organization)
Social psychology studies the "common enemy effect", the phenomenon that members of a group work together when they face an opponent, although they otherwise have little in common. An interesting scenario is the formation of an information network where group members individually sponsor costly links. Suppose that ceteris paribus, an outsider appears who aims to disrupt the information flow within the network by deleting some of the links. The question is how the group responds to this common enemy. We address this question for the homogeneous connections model of strategic network formation, with two-way flow of information and without information decay. For sufficiently low linkage costs, the external threat can lead to a more connected network, a positive common enemy effect. For very high but not prohibitively high linkage costs, the equilibrium network can be minimally connected and efficient in the absence of the external threat whereas it is always empty and ineffi cient in the presence of the external threat, a negative common enemy effect. For intermediate linkage costs, both connected networks and the empty network are Nash for certain cost ranges.

Network Formation and Disruption - An Experiment: Are equilibrium networks too complex? - Endres, Angelika Elfriede; Recker, Sonja; Mir Djawadi, Behnud; Hoyer, Britta (Journal of Economic Behavior and Organization)
Models on network formation have often been extended to include the potential of network disruption in recent years. Whereas the theoretical research on network formation under the threat of disruption has thus gained prominence, hardly any experimental research exists so far. In this paper, we therefore experimentally study the emergence of networks including the aspect of a known external threat by relating theoretical predictions by Dzuibiński and Goyal (2013) to actual observed behaviour. We deal with the question if subjects in the role of a strategic Designer are able to form safe networks for least costs while facing a strategic Adversary who is going to attack their networks. Varying the costs for protecting nodes, we designed and tested two treatments with different predictions for the equilibrium network and investigated whether one of the least cost equilibrium networks was more likely to be reached. Furthermore, the influence of the subjects’ farsightedness on their decision-making process was elicited and analysed. We find that while subjects are able to build safe networks in both treatments, equilibrium networks are only built in one of the two treatments. In the other treatment, predominantly safe networks are built but they are not for least costs. Additionally, we find that farsightedness –as measured in our experiment– has no influence on whether subjects are able to build safe or least cost equilibrium networks. Two robustness settings with a reduced external threat or more liberties to modify the initial networks qualitatively confirm our results. Overall, in this experiment observed behaviour is only partially in line with the theoretical predictions by Dzuibiński and Goyal (2013).

Determinants of Equilibrium Selection in Network Formation - An Experiment - Hoyer, Britta; Rosenkranz, Stephanie (Games)

Preemptive Repression: Deterrence, Backfiring, Iron Fists and Velvet Gloves - De Jaegher, Kris; Hoyer, Britta (Journal of Conflict Resolution)
We present a game-theoretic model of the repression–dissent nexus, focusing on preemptive repression. A small group of instigating dissidents triggers a protest if each dissident participates. The dissidents face random checks by security forces, and when an individual dissident is caught while preparing to participate, he or she is prevented from doing so. Each dissident can invest in countermeasures, which make checks ineffective. For large benefits of protest, higher preemptive repression in the form of a higher number of checks has a deterrence effect and makes dissidents less prone to invest in countermeasures, decreasing the probability of protest. For small benefits of protest, higher preemptive repression instead has a backfiring effect. Both myopic and farsighted governments avoid the backfiring effect by setting low levels of preemptive repression (velvet-glove strategy). However, only a farsighted government is able to exploit the deterrence effect by maintaining a high level of preemptive repression (iron-fist strategy).

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja
In actual school choice applications the theoretical underpinnings of the Boston School Choice Mechanism (BM) (complete information and rationality of the agents) are often not given. We analyze the actual behavior of agents in such a matching mechanism, using data from the matching mechanism currently used in a clearinghouse at a faculty of Business Administration and Economics at a German university, where a variant of the BM is used, and supplement this data with data generated in a survey among students who participated in the clearinghouse. We find that under the current mechanism over 70% of students act strategically. Controlling for students' limited information, we find that they do act rationally in their decision to act strategically. While students thus seem to react to the incentives to act strategically under the BM, they do not seem to be able to use this to their own advantage. However, those students acting in line with their beliefs manage a significantly better personal outcome than those who do not. We also run simulations by using a variant of the deferred acceptance algorithm, adapted to our situation, to show that the use of a different algorithm may be to the students' advantage.

Strategic Network Disruption and Defense - Hoyer, Britta; De Jaegher, Kris (Journal of Public Economic Theory)
We study a game between a network designer, who uses costly links to connect nodes in a network, and a network disruptor who tries to disrupt the resulting network as much as possible by deleting either nodes or links. For low linking costs networks with all nodes in symmetric positions are a best response of the designer under both link deletion and node deletion. For high linking costs the designer builds a star network under link deletion, but for node deletion excludes some nodes from the network to build a smaller but stronger network. For intermediate linking costs the designer again builds a symmetric network under node deletion but a star‐like network with weak spots under link deletion.

By-product mutualism and the ambiguous effects of harsher environments – A game-theoretic model - De Jaegher, Kris; Hoyer, Britta (Journal of Theoretical Biology)
We construct two-player two-strategy game-theoretic models of by-product mutualism, where our focus lies on the way in which the probability of cooperation among players is affected by the degree of adversity facing the players. In our first model, cooperation consists of the production of a public good, and adversity is linked to the degree of complementarity of the players׳ efforts in producing the public good. In our second model, cooperation consists of the defense of a public, and/or a private good with by-product benefits, and adversity is measured by the number of random attacks (e.g., by a predator) facing the players. In both of these models, our analysis confirms the existence of the so-called boomerang effect, which states that in a harsh environment, the individual player has few incentives to unilaterally defect in a situation of joint cooperation. Focusing on such an effect in isolation leads to the "common-enemy" hypothesis that a larger degree of adversity increases the probability of cooperation. Yet, we also find that a sucker effect may simultaneously exist, which says that in a harsh environment, the individual player has few incentives to unilaterally cooperate in a situation of joint defection. Looked at in isolation, the sucker effect leads to the competing hypothesis that a larger degree of adversity decreases the probability of cooperation. Our analysis predicts circumstances in which the "common enemy" hypothesis prevails, and circumstances in which the competing hypothesis prevails.

Do talented women shy away from competition? - Hoyer, Britta; van Huizen, Tomas; Keijzer, Linda; Rezai Khavas, Tahere; Rosenkranz, Stephanie
We study the willingness to compete in a cognitive task among an entire cohort of fresh man business and economics students. Combining data from a lab-in-thefield experiment with university admissions data, we trace the gender gap in competitiveness at different levels of high school performance. Our results confirm that, on average, men choose to compete more often. The gender gap disappears, however, among students with above average high school performance. Female high school top performers are equally competitive as their male counterparts. In fact, the overall gender gap is entirely driven by the group of female high school underperformers who shied away from competition, even when they performed well in our task. Overall, our findings suggest that high school grades are more than just a signal of cognitive abilities, because they seem to influence the receivers selfperception of his or her performance in a competitive environment involved in later on in life.

Collective action and the common enemy effect - De Jaegher, Kris; Hoyer, Britta (Defence and Peace Economics)
How is collective defence by players affected when they face a threat from an intelligent attacker rather than a natural threat? This paper analyses this question using a game-theoretic model. Facing an intelligent attacker has an effect if players move first and visibly set their defence strategies, thereby exposing any players who do not defend, and if the attacker is, moreover, not able to commit to a random attack. Depending on the parameters of the game, the presence of an intelligent attacker either increases the probability that players jointly defend (where such joint defence either does or does not constitute a utilitarian optimum), or decreases the probability that players jointly defend (even though joint defence is a utilitarian optimum).

Network Disruption and the Common Enemy Effect - Hoyer, Britta; De Jaegher, Kris
The phenomenon that groups or people work together when they face an opponent, although they have little in common otherwise, has been termed the "common enemy effect". We study a model of network formation, where players can use links to build a network, knowing that they are facing a common enemy who can disrupt the links within the network, and whose goal it is to minimize the sum of the benefits of the network. We find that introducing a common enemy can lead to the formation of stable and efficient networks as well as fragmented networks and the empty network.